2023
DOI: 10.3389/fsurg.2023.1019237
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of transvaginal repair vs. hysteroscopic resection in patients with symptomatic uterine niche

Abstract: ObjectiveTo compare the efficacy of transvaginal repair and hysteroscopic resection in improving niche associated postmenstrual spotting.MethodsThe improvement rate of postmenstrual spotting in women who underwent transvaginal repair or hysteroscopic resection treatment was assessed retrospectively in patients accepted at the Niche Sub-Specialty Clinic in International Peace Maternity and Child Health Hospital between June 2017 and June 2019. Postoperative spotting symptom within one year after surgery, pre- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…They noted that both approaches can improve spotting symptoms and restore normal lower uterine segment anatomy. Their follow up included repeat transvaginal ultrasound and identified that the transvaginal repair results in greater myometrial thickening compared to hysteroscopic resection, though the clinical significance of this is still lacking [36]. A conference abstract by Mashiach and Burke from the European Society of Human Reproduction and Embryology (ESHRE) annual conference in June 2023 presented findings from a systematic review entitled 'C-section scar defect: Hysteroscopic vs laparoscopic repair', noting similar improvement rates in bleeding symptoms and comparable pregnancy rates following both repair routes [98].…”
Section: Management Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They noted that both approaches can improve spotting symptoms and restore normal lower uterine segment anatomy. Their follow up included repeat transvaginal ultrasound and identified that the transvaginal repair results in greater myometrial thickening compared to hysteroscopic resection, though the clinical significance of this is still lacking [36]. A conference abstract by Mashiach and Burke from the European Society of Human Reproduction and Embryology (ESHRE) annual conference in June 2023 presented findings from a systematic review entitled 'C-section scar defect: Hysteroscopic vs laparoscopic repair', noting similar improvement rates in bleeding symptoms and comparable pregnancy rates following both repair routes [98].…”
Section: Management Optionsmentioning
confidence: 99%
“…&,20]; 18 retrospective cohort studies[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]; nine prospective cohort studies[39][40][41][42][43][44]45 & ,46,47]; four case controls[48][49][50][51]; three cross-sectional[52- 54]; five editorials[55][56][57][58][59]; two expert opinion articles [60 & ,61 &&…”
mentioning
confidence: 99%